Developing a Smart Campus Framework through System Dynamics Modeling - Hamdayani, Wira; Kamrijal (Moccasin Journal De Public Perspective, 2025)
This study investigates the key components and challenges associated with the implementation of a smart campus at IPDN Campus Jatinangor. The aim was to identify critical infrastructural elements required for the successful transition to a smart campus, including internet infrastructure, smart classrooms, and smart security systems. A mixed-methods approach was employed, combining qualitative interviews with faculty, staff, and students, along with system dynamics modeling to explore the complex interactions among various components of the smart campus. The results show that increased internet speed, expanded smart classrooms, and integrated security systems are essential for improving the learning environment, enhancing campus safety, and supporting efficient administrative processes. Simulation results indicated that gradual infrastructure expansion, supported by sustainable funding models, would be the most effective strategy. The study contributes to the existing body of knowledge by applying system dynamics modeling to smart campus development, providing a framework for future research on the scalability and implementation of smart campuses across higher education institutions. The findings suggest that further research could explore funding strategies and examine the role of policy in driving smart campus development.